Hyperleukocytosis and leukostasis in acute and chronic leukemias. Issue 8 (3rd July 2022) - Macaron, Walid; Sargsyan, Zaven; Short, Nicholas J.
Abstract: Leukostasis is a life-threatening complication of high concentrations of circulating leukemic cells, most often myeloblasts. Effective care of patients with leukostasis involves early recognition and treatment, and aggressive management of concurrent complications of the underlying leukemia. The relatively poor prognosis in patients with leukostasis underscores the importance of the timely and effective care of this hematologic emergency. While cytoreductive measures such as hydroxyurea, corticosteroids, intravenous chemotherapy, and leukapheresis are available to urgently reduce high cell counts, characterization of the leukemia and initiation of tailored, definitive treatment is a parallel priority. However, data supporting any specific cytoreductive approach are limited, making clinical practice guided primarily by expert opinion. In this review, we discuss the pathophysiology, clinical manifestations, diagnosis, and management of leukemic hyperleukocytosis and leukostasis, with an emphasis on how to acutely manage this oncologic emergency in patients with acute myeloid leukemia, which is the most common cause of symptomatic leukostasis.